Nano-chitosan mitigates lead acetate-induced histological changes in rat testicular seminiferous tubules - Muhammad Daffa Dyarizky Ramadhan; Aditya Marianti; Rahma Anindita (Acta Scientiarum. Biological Sciences, 2024)
Lead is a toxic metal known to be harmful once within the body. Chronic lead accumulation causes the emergence of free radicals, thereby causing damage to organ systems, one of which is the reproductive system. Chitosan can chelate lead metal ions which behave as free radicals. In nanostructures, chitosan's ability to chelate heavy metal ions is expected to be more effective. The use of nano-chitosan is expected to facilitate its distribution so that its ability to chelate lead ions is more effective. This study aims to analyze the effect of nano-chitosan on the histology of seminiferous tubules and spermatogenesis of rats induced by lead acetate (PbAc). Animals are divided into 3 groups; Naive Group (NG: aquadest), Positive Control (PC: PbAc 200 mg kg-1 BW), Treatment Group (TG: PbAc 200 mg kg-1 BW and nano-chitosan 64 mg kg-1 BW) with a treatment duration of 35 days, and 6 rats in each group. Rats were exposed to lead by oral administration. At the end of the treatment period, animals were euthanized by dislocation of the cervical spine after being lightly anesthetized using 10% chloroform. Then, testicular organs were dissected, and histological preparations of the seminiferous tubules were analyzed. Measurements include epithelial thickness, tubule diameter and spermatogenesis scoring based on the Johnson criteria. The results obtained proved that administration of nano-chitosan after PbAc induction increased epithelial thickness, seminiferous tubule diameter and spermatogenesis score. In conclusion, nano-chitosan can overcome lead toxicity in the rat reproductive system induced by PbAc with indicators of improvement in the histology structure of seminiferous tubules and increased spermatogenesis scores.